Transcriptomic analysis provides a new insight: Oleuropein reverses high glucose-induced osteogenic inhibition in bone marrow mesenchymal stem cells via Wnt10b activation - Lao, An; Chen, Yu; Sun, Yiting; Wang, Tiange; Lin, Kaili; Liu, Jiaqiang; Wu, Jianyong (Frontiers in Bioengineering and Biotechnology, 2022)
Adverse events of diabetes mellitus (DM) include bone damages, such as the increased incidence of osteoporosis and bone fractures, which are known as diabetic osteopathy. The pathogenic mechanism of diabetic osteopathy is complex, and hyperglycemia is a vital cause involved in it. Bone marrow mesenchymal stem cells (BMSCs) exert a significant effect on bone formation. Therefore, in this paper, transcriptomic changes of BMSCs cultured in high glucose (35mM) for 30 days are mainly investigated. In addition, 794 up-regulated genes and 1162 down-regulated genes were identified. Then, biological functions of the differentially expressed genes (DEGs) in the high glucose microenvironment were investigated by two kinds of functional analyses. Gene Set Enrichment Analysis (GSEA) was also applied to focus on the significant gene sets and it is found that Wnt10b expression witnessed a remarkable decrease in BMSCs under the high glucose microenvironment. At last, in vitro experiments revealed that oleuropein effectively reversed high glucose-induced osteogenic inhibition via activating Wnt10b in BMSCs.